Comparative performances, under laboratory conditions, of seven pyrethroid insecticides used for impregnation of mosquito nets - Hougard Jean-Marc; Duchon Stéphane; Darriet Frédéric; Zaim Morteza; Rogier Christophe; Guillet Pierre (The World Health Organization, 2003)
Objective: To compare the efficacy of seven pyrethroid insecticides for impregnation of mosquito nets, six currently recommended by WHO and one candidate (bifenthrin), under laboratory conditions. Methods: Tests were conducted using pyrethroid-susceptible and pyrethroid-resistant strains of Anopheles gambiae and Culex quinquefasciatus. Knock-down effect, irritancy and mortality were measured using standard WHO cone tests. Mortality and blood-feeding inhibition were also measured using a baited tunnel device. Findings: For susceptible A. gambiae, alpha-cypermethrin had the fastest knock-down effect. For resistant A. gambiae, the knock- down effect was slightly slower with alpha-cypermethrin and much reduced following exposure to the other insecticides, particularly bifenthrin and permethrin. For susceptible C. quinquefasciatus, the knock-down effect was significantly slower than in A. gambiae, particularly with bifenthrin, and no knock-down effect was observed with any of the pyrethroids against the resistant strain. Bifenthrin was significantly less irritant than the other pyrethroids to susceptible and resistant A. gambiae but there was no clear ranking of pyrethroid irritancy against C. quinquefasciatus. In tunnels, all insecticides were less toxic against C. quinquefasciatus than against A. gambiae for susceptible strains. For resistant strains, mortality was significant with all the pyrethroids with A. gambiae but not with C. quinquefasciatus. Inhibition of blood-feeding was also high for susceptible strains of both species and for resistant A. gambiae but lower for resistant C. quinquefasciatus; bifenthrin had the greatest impact. Conclusions: Efficacy for impregnation of mosquito nets against A. gambiae was greatest with alpha-cypermethrin. Bifenthrin is likely to have a significant comparative advantage over other pyrethroids in areas with pyrethroid resistance because of its much stronger impact on the nuisance mosquito, C. quinquefasciatus, despite its slower knock-down effect and irritancy. Selection of pyrethroids for mosquito vector control and personal protection should take into account the different effects of these insecticides, the status of pyrethroid resistance in the target area, and the importance of nuisance mosquitoes, such as C. quinquefasciatus.